2016
DOI: 10.14202/vetworld.2017.398-402
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study on bovine mastitis and its associated risk factors in Ambo district of West Shewa zone, Oromia, Ethiopia

Abstract: Aim:A cross-sectional study was conducted to estimate the prevalence and associated risk factors of mastitis in dairy cows.Materials and Methods:A total of 302 dairy cows were selected from all volunteer dairy farms in Ambo district of West Shewa Zone, Oromia region. Thorough clinical examination was made on all lactating cows for evidence of signs of clinical mastitis followed by collection of milk sample for examination of gross changes of milk secretion and California mastitis test.Result:About 126 (41.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
9
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
(5 reference statements)
9
9
4
1
Order By: Relevance
“…This study reported a higher prevalence of subclinical mastitis (74%) than clinical (7%) mastitis. These findings agree with other studies by Zeryehun and Abera [ 13 ] and as reported elsewhere by [ 3 , 39 ]. These significant differences could be attributed to the fact that clinical mastitis can easily be diagnosed and treated [ 4 ], whereas, on the other hand, the subclinical form has no physical abnormalities; hence, it is hardly diagnosed by the farmers and continues to be a source of infection in the farm [ 2 , 43 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study reported a higher prevalence of subclinical mastitis (74%) than clinical (7%) mastitis. These findings agree with other studies by Zeryehun and Abera [ 13 ] and as reported elsewhere by [ 3 , 39 ]. These significant differences could be attributed to the fact that clinical mastitis can easily be diagnosed and treated [ 4 ], whereas, on the other hand, the subclinical form has no physical abnormalities; hence, it is hardly diagnosed by the farmers and continues to be a source of infection in the farm [ 2 , 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…The present study reported clinical mastitis of 6.8%. These findings were closely related to what was reported by Sarba and Tola [ 39 ], 9.9%, and Zeryehun and Abera [ 13 ], 10%, in Ethiopia. However, they were lower than findings by Amer et al [ 18 ] in Japan, who reported a prevalence of 12%, Tolosa et al [ 38 ] and Mekibib et al [ 40 ] in Ethiopia, and Levison et al [ 41 ] in Canada, who reported prevalence of 12%, 11%, 22.7%, and 23%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…But, the result was higher than 2.6% [23] 3.75% in and around Wolaita Sodo [26] and 3% in and around Bahir Dar [27]. However, the current finding was lower than 9.9% reported [28] in Ambo, central Ethiopia.…”
Section: Discussioncontrasting
confidence: 71%
“…A lack of screening SCM and late or not treating clinical cases could lead to acquired blindness of mammary gland. Blind mammary quarters contribute to high SCM and loss of milk production with a subsequent impact on food security [43].…”
Section: Discussionmentioning
confidence: 99%